A documentary analysis of teacher education trends in the United States and in the Philippines and its implications for enrichment of the three-month in-service education programme in Korea - Yoon, Hei Joon 1931- (s.n.], 1967)
This study analyzed the principles, trends and practices of in-service education programmes in the United States and in the Philippines through documentary analysis with a view of deriving implications for enriching the three-month regular in-service education programme for elementary school teachers given at the In-Service Education Institute of Korea.